USAHA KRIPIK NABATI: MANAJEMEN USAHA DAN PROSES PRODUKSI (STUDI PADA KELOMPOK WANITA TANI (KWT) SEJAHTERA DESA KOPEN TERAS BOYOLALI) - Sri Suranta; Halim Dedy Perdana; Muhammad Syafiqurrahman (LPPM UNS, 2016)
The purpose of the implementation of Community Services (PPM) is to improve the quality and quantity of production and improve the management of business on the business Vegetable Chips on Women Farmers Group